UiO-66 / g-C3N4 / SA photocatalyst for remediating wastewater containing dimethyl phthalate (DMT) micro-contamination

CN120571638BActive Publication Date: 2026-10-16NORTHEAST NORMAL UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510423968.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-04-07
Publication Date
2026-10-16
Estimated Expiration
2045-04-07

AI Technical Summary

Technical Problem

[0006]单一光催化剂(如g-C3N4或UiO-66)的吸附能力与催化活性难以兼顾,且粉体催化剂易团聚、难回收

Benefits of technology

通过UiO-66/g-C3N4大的比表面积、丰富的官能团提升对邻苯二甲酸二甲酯的吸附,通过其Z型异质结结构提升光照下对邻苯二甲酸二甲酯的原位降解、矿化能力。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120571638B_ABST
    Figure CN120571638B_ABST
Patent Text Reader

Abstract

The present application relates to a kind of for repairing dimethyl phthalate micro-polluted wastewater UiO-66 / g-C3N4 / SA photocatalyst, by the large specific surface area of UiO-66 / g-C3N4, rich functional group promotes the adsorption of dimethyl phthalate, by its Z type heterojunction structure promotes in situ degradation under illumination to dimethyl phthalate, mineralization capacity;For containing humic acid, Cl⁻, Fe³⁺And other complex water body, and in ultrapure water, tap water and well water etc. Water base, UiO-66 / g-3N4 / SA shows higher removal rate to micro-polluted dimethyl phthalate, the highest removal rate of 0.1 mg / L dimethyl phthalate can reach 93% in 60 minutes, and mineralization rate reaches 43%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of wastewater treatment technology, specifically relating to a UiO-66 / g-C3N4 / SA photocatalyst and its application in the remediation of micro-polluting dimethyl phthalate water treatment. Background Technology

[0002] The commissioning and upgrading of urban and industrial wastewater treatment plants have effectively alleviated traditional water pollution problems such as black and odorous water bodies and eutrophication. However, their effectiveness in removing micro-pollutants with low concentrations (ng / L-μg / L) and poor biodegradability in water bodies is very limited, posing a potential new type of water pollution problem. Dimethyl phthalate (DMT) is one of the most widely used endocrine disruptors with a simple chemical structure. During manufacturing, application, and treatment, it easily migrates into soil, atmosphere, and water, and can gradually accumulate in the food chain through bioaccumulation, exhibiting endocrine disrupting, carcinogenic, or estrogens characteristics. It has been listed as a priority pollutant by the U.S. Environmental Protection Agency. Developing efficient and environmentally friendly treatment technologies to remove DMT from the environment is urgently needed.

[0003] Photocatalysis, utilizing solar energy to excite semiconductors, has attracted widespread attention due to its advantages such as being clean and friendly, having mild reaction conditions, being simple to operate, and producing no secondary pollution. The main challenges in photocatalytic removal of micro-pollutants are poor mass transfer and low quantum efficiency. Photocatalysis is a typical heterogeneous reaction, and its degradation capacity is positively correlated with the catalyst's adsorption affinity for pollutants. When pollutant concentrations are low, the gradient from the water body to the catalyst surface is small, and intermolecular collisions and diffusion are poor, inhibiting mass transfer. Charge carriers generated after photoexcitation of the catalyst can undergo recombination or reach the catalyst surface to degrade pollutants. If there are insufficient charge carriers, pollutants may not degrade or may lead to the combination of intermediate substances with other substances to form byproducts, hindering mineralization or even producing toxins. Therefore, constructing dual-functional purification materials that combine "enrichment enhancement and catalytic degradation" to address the problems of enhanced enrichment and in-situ catalytic degradation of micro-pollutants under low driving forces is imperative.

[0004] g-C3N4 exhibits excellent thermal and chemical stability under high temperatures and various chemical environments, demonstrating superior performance in photocatalytic water splitting, carbon dioxide reduction, and pollutant degradation. However, its inherent limitations (such as low conductivity and photogenerated carrier separation efficiency) still require further optimization through strategies such as surface modification and heterostructure construction.

[0005] UiO-66 is a zirconium (Zr)-based metal-organic framework (MOF) with a highly ordered porous structure and excellent physicochemical stability. It can be combined with other materials (such as carbon nanofibers and graphene oxide) to form composite materials with even higher performance. For example, the UiO-66 / HOCN composite material has shown high efficiency in detecting pesticide residues in black tea. In-situ synthesis of UiO-66 nanoparticle membranes on wood substrates has been used to treat cationic water-soluble organic dyes, achieving a removal rate exceeding 96%. Significant progress has been made in the in-situ hydrothermal method of UiO-66, not only diversifying the synthesis methods but also demonstrating broad application potential in multiple fields such as battery membranes, water treatment, catalysis, and adsorption. Further research will optimize the synthesis conditions and explore more functionalization modification methods to enhance the performance and application range of UiO-66.

[0006] Single photocatalysts (such as g-C3N4 or UiO-66) struggle to simultaneously achieve both adsorption capacity and catalytic activity, and powdered catalysts are prone to agglomeration and difficult to recover. There is a need to research novel materials that possess both adsorption-catalysis dual functions, are easily separable, and have broad applicability. Various g-C3N4-based heterojunction materials, such as CdS / g-C3N4, CuS / g-C3N4, and ZnO / g-C3N4, have shown significant performance improvements in photocatalytic water splitting, hydrogen production, and organic pollutant degradation. For example, the CdS / g-C3N4 heterojunction exhibits higher photocatalytic efficiency and stability in the photocatalytic hydrogen evolution reaction (HER) than pure g-C3N4. Future research requires further optimization of the synthesis conditions of g-C3N4 and its composites, improvement of the composite material performance, and exploration of more practical applications. Summary of the Invention

[0007] The purpose of this invention is to provide a UiO-66 / g-C3N4 / SA photocatalyst, which improves the catalyst's recyclability by loading UiO-66 / g-C3N4 onto the microsphere carrier SA, and is suitable for the efficient purification of water bodies polluted with low concentrations and recalcitrant dimethyl phthalate.

[0008] The objective of this invention is achieved through the following technical solution: A UiO-66 / g-C3N4 / SA photocatalyst includes the following steps: g-C3N4 was added to the UiO-66 precursor solution and reacted in a reactor at 120 °C for 24 h. After washing and drying, the product was obtained. UiO-66 / g-C3N4 was dispersed in an aqueous solution of sodium alginate (SA) and then added dropwise to a collection solution containing calcium ions to form a UiO-66 / g-C3N4 / SA photocatalytic functional material.

[0009] As a preferred technical solution of the present invention, the preparation process of g-C3N4 is as follows: Place the urea in a crucible, and add 0.5... o C·min -1 The rate of heating increases to 550 o The product was kept at 60°C for 3 hours, cooled to room temperature, washed with deionized water and ethanol, and centrifuged to obtain a pale yellow product. o After vacuum drying at C for 8 h, a light yellow powder was obtained, namely the pure phase g-C3N4.

[0010] As a preferred technical solution of the present invention, the preparation steps of UiO-66 are as follows: Terephthalic acid was dissolved in N,N-dimethylformamide, and glacial acetic acid was slowly added dropwise after stirring. Zirconium chloride was dissolved in N,N-dimethylformamide and stirred. The two solutions were then mixed and transferred to a reaction vessel lined with polytetrafluoroethylene. The mixture was then heated to 120 °C. o After being kept at C for 24 h, washed with N,N-dimethylformamide and ethanol, it was then kept at 60 °C. o Vacuum drying at C for 8 h yielded pure phase UiO-66.

[0011] As a more preferred technical solution of the present invention, the mass ratio of UiO-66 and g-C3N4 is 0.6-1.0.

[0012] As a more preferred technical solution of the present invention, the mass ratio of UiO-66 and g-C3N4 is 0.6.

[0013] As a preferred technical solution of the present invention, the concentration of the SA aqueous solution is 10-16 g / L.

[0014] As a preferred technical solution of the present invention, the preparation process of the collection liquid is as follows: Add 2% calcium chloride, calcium gluconate, or calcium lactate to deionized water and mix thoroughly to obtain the collection solution.

[0015] As a more preferred technical solution of the present invention, the mass ratio of SA to UiO-66 / g-C3N4 is 10-16.

[0016] As a more preferred technical solution of the present invention, the mass ratio of SA to UiO-66 / g-C3N4 is 10.

[0017] Another object of this invention is to use the above-mentioned UiO-66 / g-C3N4 / SA photocatalyst to remove dimethyl phthalate from wastewater, comprising the following steps: The UiO-66 / g-C3N4 / SA photocatalyst was added to water containing dimethyl phthalate to adsorb and enrich pollutants. Photocatalytic degradation is carried out under a light source with a wavelength of 300-780 nm to achieve the removal and mineralization of pollutants.

[0018] As a preferred technical solution of the present invention, the dosage of the UiO-66 / g-C3N4 / SA photocatalyst is 1-3 g / L.

[0019] The beneficial effects of this invention are as follows: The large specific surface area and abundant functional groups of UiO-66 / g-C3N4 enhance the adsorption of dimethyl phthalate, and its Z-shaped heterojunction structure enhances the in-situ degradation and mineralization of dimethyl phthalate under light irradiation.

[0020] For complex water bodies containing humic acid, Cl⁻, Fe³⁺, etc., and in water matrices such as ultrapure water, tap water and well water, UiO-66 / g-C3N4 / SA exhibits a high removal rate of dimethyl phthalate with slight pollution. The highest removal rate of 0.1 mg / L dimethyl phthalate can reach 93% within 60 minutes, and the mineralization rate reaches 43%.

[0021] After 12 cycles of cycling performance testing, the degradation efficiency remained above 89%, and the cycling stability was significantly better than that of unloaded powder catalysts. It has good recyclability and can be beneficial to the remediation of aquatic environments. Attached Figure Description

[0022] Figure 1 Scanning electron microscope (SEM) images of g-C3N4 (a), UiO-66 (b), and UiO-66 / g-C3N4 (c) prepared in Example 1 of this invention, showing specific surface area (d), light absorption (e), and internal electric field and charge transfer diagrams (f) of UiO-66 / g-C3N4.

[0023] Figure 2 The graphs show the adsorption (a), degradation curve (b), and TOC degradation curve (c) of dimethyl phthalate in Example 2 of this invention.

[0024] Figure 3 The removal curves of atrazine (ATZ) (a), tetracycline hydrochloride (TCH) (b), sulfamethoxazole (SMZ) (c), and bisphenol A (BPA) (d) in Comparative Example 1 of this invention are shown.

[0025] Figure 4 Photographs and scanning electron microscope images of SA microbeads (a) and UiO-66 / g-C3N4 / SA photocatalyst (be) prepared for Example 3 of the present invention, as well as X-ray photoelectron spectroscopy (f) and Fourier transform infrared spectrum (g) of the materials.

[0026] Figure 5 This is a diagram of the photocatalyst reaction apparatus in this invention.

[0027] Figure 6 The graphs show the removal curve (a) and TOC degradation curve (b) of dimethyl phthalate in Example 4 of this invention.

[0028] Figure 7 The removal curves of atrazine (ATZ) (a), tetracycline hydrochloride (TCH) (b), sulfamethoxazole (SMZ) (c), and bisphenol A (BPA) (d) in Comparative Example 3 of this invention are shown.

[0029] Figure 8 This is a graph showing the effect of the initial concentration of dimethyl phthalate (a), the amount of functional material (b), and the coexisting substances (c) on the degradation efficiency of dimethyl phthalate in Example 5 of the present invention.

[0030] Figure 9 The image shows the removal effect of the UiO-66 / g-C3N4 / SA photocatalyst in different aqueous matrices in Example 6 of this invention on dimethyl phthalate.

[0031] Figure 10 The results are the cyclic test results of the 0.6-UiO-66 / g-C3N4 and 0.6-UiO-66 / g-C3N4 / 10-SA functional materials in Example 7 of this invention.

[0032] Figure 11 The results are based on the cyclic testing of the 0.2-UiO-66 / g-C3N4 and 0.2-UiO-66 / g-C3N4 / 10-SA functional materials in Comparative Example 4 of this invention. Detailed Implementation

[0033] The present invention will be further described in detail below with reference to specific embodiments. The embodiments given are only for illustrating the present invention and are not intended to limit the scope of the present invention. The embodiments provided below can serve as a guide for further improvements by those skilled in the art and do not constitute a limitation on the present invention in any way.

[0034] Unless otherwise specified, the experimental methods used in the following examples are conventional methods, performed according to the techniques or conditions described in the literature in this field or according to the product instructions. Unless otherwise specified, the materials and reagents used in the following examples are commercially available.

[0035] In this invention, the preferred mass ratio of UiO-66 to g-C3N4 in the UiO-66 / g-C3N4 composite photocatalyst is 0.6. In the embodiments, the specific mass ratios are 0.2, 0.4, 0.6, 0.8, and 1.0. The preferred mass ratio of SA to UiO-66 / g-C3N4 composite photocatalyst in the UiO-66 / g-C3N4 / SA photocatalytic functional material is 10. In the embodiments, the specific mass ratios are 10, 12, 14, and 16.

[0036] The technical solutions of this invention will be clearly and completely described below with reference to the embodiments thereof. The described embodiments are merely some embodiments of this invention, and not all embodiments. All other embodiments obtained by those skilled in the art based on the embodiments of this invention without creative effort are within the scope of protection of this invention.

[0037] The preparation process of the UiO-66 / g-C3N4 / SA photocatalytic functional material provided by this invention involves first preparing pure-phase g-C3N4, and then preparing the UiO-66 / g-C3N4 composite photocatalyst. The pure-phase g-C3N4 is prepared by high-temperature calcination and centrifugal drying. The UiO-66 / g-C3N4 composite photocatalyst is prepared hydrothermally by adding pure-phase g-C3N4 to a UiO-66 precursor solution. The UiO-66 / g-C3N4 photocatalyst is prepared by dispersing the UiO-66 / g-C3N4 photocatalyst material on a sodium alginate (SA) matrix and utilizing the crosslinking reaction between SA and calcium ions. This includes the preparation of an aqueous fluid, the preparation of a collection liquid, and the mixing of the aqueous fluid and the collection liquid. The high-temperature calcination conditions include the heating rate, maximum temperature, and holding time; the drying conditions include the drying temperature and drying time. The preparation of the UiO-66 / g-C3N4 composite photocatalyst requires control of the precursor solution composition, hydrothermal temperature, and time. Controlling the mass ratio of UiO-66 to g-C3N4 is achieved by changing the amount of pure-phase g-C3N4 added to obtain the x-UiO-66 / g-C3N4 series composite photocatalysts, where x represents the mass ratio of UiO-66 to g-C3N4. The mass ratio of SA to UiO-66 / g-C3N4 / SA needs to be controlled. The optimal mass ratio of UiO-66 to g-C3N4 is selected as 0.6-UiO-66 / g-C3N4. 0.6-UiO-66 / yg-C3N4 is prepared by changing the amount of SA, where y is the mass ratio of SA to 0.6-UiO-66 / g-C3N4.

[0038] In this embodiment of the invention, the optimal dual ratio of the UiO-66 / g-C3N4 / SA photocatalytic functional material is determined through adsorption-in-situ photocatalysis. The adsorption-in-situ photocatalysis includes two processes: adsorption and photocatalytic degradation. The adsorption and photocatalytic degradation processes require control of the ambient temperature during adsorption, the initial concentration of dimethyl phthalate, and the wavelength range and light intensity of the light source during photocatalytic degradation.

[0039] This invention examines the effects of environmental factors on the degradation of dimethyl phthalate by the UiO-66 / g-C3N4 / SA photocatalytic functional material to evaluate the optimal usage conditions of the material. These factors include initial concentration, catalytic material dosage, and coexisting substances. The coexisting substances include common dissolved organic matter, anions, and cations in water, specifically humic acid and Cl-. - NO3 - NH4 + Fe 3+ .

[0040] In this embodiment of the invention, the removal efficiency of the UiO-66 / g-C3N4 / SA photocatalytic functional material for dimethyl phthalate (DMT), a micro-pollutant, was investigated in different water matrices, and the recyclability of the material was evaluated. The different water matrices included ultrapure water, tap water, well water, and secondary effluent from wastewater treatment plants.

[0041] Example 1 The steps for preparing the UiO-66 / g-C3N4 composite photocatalyst include solution preparation and hydrothermal treatment.

[0042] The preparation steps of pure-phase g-C3N4 material include high-temperature calcination and centrifugal drying: High-temperature calcination: Place an appropriate amount of urea in a crucible, and calcine at 0.5... o C·min -1 The rate of heating increases to 550 o Keep at C for 3 hours. After cooling to room temperature, wash with deionized water and ethanol.

[0043] Centrifugal drying: The pale yellow product obtained after centrifugation is dried at 60°C. o After vacuum drying at C for 8 h, a light yellow powder was obtained, namely the pure phase g-C3N4.

[0044] The preparation steps of pure phase UiO-66 include solution preparation and hydrothermal treatment: Solution preparation: Dissolve 1.24 mmol of terephthalic acid in 10 mL of N,N-dimethylformamide, stir for 30 min, and then slowly add 2.50 mL of glacial acetic acid; dissolve 1.37 mmol of zirconium chloride in 10 mL of N,N-dimethylformamide and stir for 30 min.

[0045] Hydrothermal: Transfer the mixture to a 50 mL polytetrafluoroethylene-lined reactor and heat at 120°C. o Keep at C for 24 h, wash with N,N-dimethylformamide ethanol, and then at 60 °C. o Vacuum drying at C for 8 h yielded pure phase UiO-66.

[0046] The preparation process of UiO-66 / g-C3N4 is as follows: Different masses of pure phase g-C3N4 powder (the mass ratio of UiO-66 to g-C3N4 was 0.2, 0.4, 0.6, 0.8, and 1.0) were added to the precursor solution prepared above to obtain x-UiO-66 / g-C3N4 (x=0.2, 0.4, 0.6, 0.8, and 1.0).

[0047] Scanning electron microscope (SEM) images of the pure-phase g-C3N4 prepared above are shown below. Figure 1 a. Its typical thin, gauze-like structure is beneficial for the loading of UiO-66 and its contact with pollutants. The pure-phase UiO-66 prepared above exhibits a regular octahedral structure with a smooth surface and an average particle size between 200-300 nm. Figure 1 b). A scanning electron microscope (SEM) image of the preferred 0.6-UiO-66 / g-C3N4 composite material is shown below. Figure 1 c. UiO-66 particles are densely distributed on the surface of g-C3N4, resulting in a higher specific surface area and better light absorption ( Figure 1 de). The formation process of Z-type heterojunctions is as follows: Figure 1 f. When the two semiconductors are combined, the charge is redistributed at the interface between them. Photogenerated electrons are transferred from UiO-66 to g-C3N4, while the holes generated at the same time migrate in the opposite direction. Finally, a built-in electric field is formed at the interface, which can effectively promote the separation of photogenerated electron-hole pairs and improve photocatalytic efficiency.

[0048] Example 2 The adsorption-photocatalytic effect of the pure-phase g-C3N4, pure-phase UiO-66, and UiO-66 / g-C3N4 series composite photocatalysts on dimethyl phthalate was investigated in Example 1. The steps are as follows: Adsorption experiment: Under neutral and dark conditions, 25 mg of catalyst was dispersed in a dimethyl phthalate solution with C0 = 0.1 mg / L and V = 100 mL, and treated in a constant temperature water bath shaker (70 rpm / min) at 20 ℃. Samples were taken and filtered at set time intervals of 5, 15, 30, 60, 90, 120, and 150 min, and the dimethyl phthalate concentration was determined using high performance liquid chromatography (HPLC). The adsorption capacity of a unit mass of adsorbent for dimethyl phthalate under equilibrium conditions can be calculated using the following formula.

[0049] QUOTE Among them, Q t (mg / g) represents the amount of adsorbent adsorbed at time t; C0 (mg / L) and C t (mg / L) represent the initial concentration of dimethyl phthalate and the concentration at time t, respectively; m (g) and V (mL) represent the adsorbent mass and solution volume, respectively.

[0050] Photocatalysis experiment: A CEL-HXF300D2 xenon lamp was used with a wavelength of 300-780 nm and a light intensity of 100 mW / cm². 2 The photocatalysis was performed using energy. The initial concentration of dimethyl phthalate was 0.1 mg / L, and the amount of powdered catalyst was 25 mg. Before irradiation, the system was kept in the dark for 90 min to achieve adsorption-desorption equilibrium between the catalyst and the pollutant. During the photocatalysis process, a certain amount of solution was taken every 20 min, filtered, and analyzed using high-performance liquid chromatography (HPLC) to determine its mineralization degree.

[0051] The test results of this embodiment are as follows: Figure 2 As shown, among the x-UiO / CN composite materials, 0.6-UiO / CN exhibits the best adsorption performance, highlighting the importance of appropriate UiO-66 loading for improving the saturated adsorption capacity of the material. It also exhibits the highest pollutant removal efficiency, due to the simultaneous excitation of both semiconductors, which increases the number of photocatalytic charge carriers, and the strong built-in electric field between UiO-66 and g-C3N4 promoting electron / hole pair separation and maintaining the strong redox ability of photogenerated charge carriers. The mineralization rate of dimethyl phthalate by 0.6-UiO-66 / g-C3N4 is 63.50%, significantly higher than that of the single material. Compared to P25, the most widely used photocatalytic material currently, all composite materials except 0.2-UiO-66 / g-C3N4 demonstrate superior photocatalytic activity.

[0052] Comparative Example 1 The removal effects of pure-phase g-C3N4, pure-phase UiO-66, and UiO-66 / g-C3N4 series composite photocatalysts on four pollutants—atrazine, tetracycline hydrochloride, sulfamethoxazole, and bisphenol A—were investigated in Example 1. The concentrations of the three pollutant solutions were controlled at CO = 0.1 mg / L and V = 100 mL, and the adsorption-photocatalytic degradation was carried out according to the steps in Example 1.

[0053] The test results of this comparative example show that, compared with the removal of dimethyl phthalate, the UiO-66 / g-C3N4 series composite photocatalyst has a better effect on the removal of atrazine (… Figure 3 a) Tetracycline hydrochloride ( Figure 3 b) Sulfamethoxazole ( Figure 3 c) and bisphenol A ( Figure 3 d) The degradation of the four pollutants was not significant, with the removal of atrazine showing the worst effect (<20%). This is because the pore size and charge of UiO-66 / g-C3N4 are mismatched with the pollutant molecules, making it difficult for the pollutants to reach the catalyst surface. Additionally, the catalytic mechanism of the composite material is mismatched with the structure of the pollutants, ultimately limiting the adsorption-photocatalytic degradation of atrazine, tetracycline hydrochloride, sulfamethoxazole, and bisphenol A.

[0054] Example 3 The steps for preparing the UiO-66 / g-C3N4 / SA photocatalyst are as follows: Preparation of aqueous phase fluid: Disperse 0.6-UiO-66 / g-C3N4 in 10 mL of deionized water, sonicate for 10 min, and then add it to 100 mL of deionized water containing 1.0 g, 1.2 g, 1.4 g, and 1.6 g of SA, respectively, and stir continuously until homogeneous.

[0055] Preparation of the collection solution: Add 2% calcium chloride to deionized water and mix well to obtain the collection solution.

[0056] The aqueous phase fluid was added dropwise to the collection liquid at a constant flow rate using a syringe. After standing for 24 hours, the solution was repeatedly rinsed with deionized water to obtain 0.6-UiO-66 / g-C3N4 / y-SA (y=10, 12, 14, 16).

[0057] Comparative Example 2: SA microbeads were prepared in this comparative example, and the steps are as follows: SA aqueous solution was added dropwise to 2% calcium chloride solution at a constant flow rate using a syringe. After standing for 24 hours, the solution was repeatedly rinsed with deionized water to obtain SA microbeads.

[0058] Images of the morphology and size of SA and UiO-66 / g-C3N4 / SA photocatalysts are shown below. Figure 4 Scanning electron microscope (SEM) images of the UiO-66 / g-C3N4 / SA photocatalyst are shown below. Figure 4 The cross-linked UiO-66 / g-C3N4 / SA photocatalyst has a rough surface with numerous wrinkles and striations, which increases the specific surface area of ​​the microspheres, providing more reaction sites for the photocatalyst and improving its adsorption capacity for pollutants. The X-ray diffraction and Fourier transform infrared spectra of the UiO-66 / g-C3N4 / SA photocatalyst are... Figure 4 fg.

[0059] Example 4 The adsorption-photocatalytic degradation performance of dimethyl phthalate by the UiO-66 / g-C3N4 / SA series photocatalyst in Example 3 and the SA microspheres in Comparative Example 2 was investigated. The amount of microspheres was controlled at 250 mg, and the adsorption-photocatalytic degradation was consistent with that in Example 2.

[0060] The removal curve of dimethyl phthalate is as follows: Figure 6 As shown in Figure a. While pure SA exhibits some adsorption for dimethyl phthalate, its photocatalytic activity is relatively low. The 0.6-UiO-66 / g-C3N4 / 10-SA functional material achieved highly efficient removal of dimethyl phthalate within 60 min. TOC degradation curve ( Figure 6 b) shows that 0.6-UiO-66 / g-C3N4 / 10-SA achieves a mineralization rate of 43% for dimethyl phthalate. This indicates that an appropriate proportion of SA can enhance the adsorption effect of the photocatalyst while maintaining its photocatalytic performance and mineralization capacity.

[0061] Comparative Example 3 The adsorption-photocatalytic degradation performance of the UiO-66 / g-C3N4 / SA series photocatalyst in Example 3 and the SA microbeads in Comparative Example 2 on three pollutants—atrazine, tetracycline hydrochloride, and metronidazole—was investigated. The amount of microbeads was controlled at 250 mg, and the adsorption-photocatalytic degradation was consistent with that in Example 2.

[0062] Atrazin ( Figure 7 a) Tetracycline hydrochloride ( Figure 7 b), sulfamethoxazole ( Figure 7 c) and bisphenol A ( Figure 7 d) The adsorption-photocatalytic degradation results of the four pollutants showed that the photocatalytic functional material improved the degradation effect of the four pollutants compared with the powder catalyst, which was due to the increase in specific surface area after loading. However, the overall removal effect was still poor, indicating the specificity of UiO-66 / g-C3N4 / SA photocatalytic functional material in the treatment of dimethyl phthalate micropollutant water.

[0063] Example 5 The effects of the UiO-66 / g-C3N4 / SA photocatalyst prepared in Example 3 on the removal efficiency of dimethyl phthalate under different initial concentrations of dimethyl phthalate, different amounts of UiO-66 / g-C3N4 / SA, and different coexisting ions were investigated. The steps are as follows.

[0064] (1) The initial concentration of dimethyl phthalate was changed to 0.05, 0.10, 0.20 and 0.30 mg / L, respectively, and the degradation was carried out according to the method in Example 4; (2) Change the amount of 0.6-UiO-66 / g-C3N4 / 10-SA photocatalyst to 0.10, 0.15, 0.25 and 0.30 g respectively, and degrade dimethyl phthalate according to the method in Example 4; (4) Add 50 μmol / L of humic acid (HA), hydrochloric acid (HCl), potassium nitrate (KNO3), ammonia (NH3·H2O) and ferric chloride (FeCl3) to the dimethyl phthalate solution to be degraded, respectively, to simulate the coexisting substances in the environment, and degrade the dimethyl phthalate according to the method in Example 4.

[0065] The test results of steps 1 and 2 in this embodiment are as follows: Figure 8 As shown in ab, the photocatalytic degradation efficiency of dimethyl phthalate was highest when the initial concentration was 0.1 mg / L and the amount of functional material was 250 mg. The tests in step 3 showed that ( Figure 8 c) Humic acid and coexisting anions and cations, either by adsorbing onto the catalyst surface and occupying active sites, or by consuming photogenerated charge carriers, can inhibit the removal of dimethyl phthalate to some extent.

[0066] Example 6 The suitability of the 0.6-UiO-66 / g-C3N4 / 10-SA photocatalyst prepared in Example 3 for the degradation of dimethyl phthalate under environmental conditions was investigated.

[0067] Dimethyl phthalate with an initial concentration of 0.1 mg / L was dissolved in four different substrate waters: ultrapure water, tap water, well water, and secondary effluent from a wastewater treatment plant, and the dimethyl phthalate was degraded according to the method in Example 4.

[0068] The test results of this embodiment show that the UiO-66 / g-C3N4 / SA photocatalytic functional material performs best in ultrapure water, while its performance in tap water and well water is somewhat inhibited due to active site shielding or photogenerated carrier consumption, resulting in a decrease in the removal efficiency of dimethyl phthalate in the secondary effluent. Figure 9 ).

[0069] Example 7 The reusability of the 0.6-UiO-66 / g-C3N4 / 10-SA photocatalyst prepared in Example 3 was investigated.

[0070] The 0.6-UiO-66 / g-C3N4 prepared in Example 1 and the 0.6-UiO-66 / g-C3N4 / 10-SA prepared in Example 3 were repeatedly used 12 times according to the methods of Example 2 and Example 4, respectively, and their degradation efficiency for dimethyl phthalate was recorded.

[0071] The results of this embodiment are as follows: Figure 10 As shown, after 12 cycles, the dimethyl phthalate degradation rate of 0.6-UiO-66 / g-C3N4 / 10-SA remained at a high level (89.09%), significantly higher than that of 0.6-UiO-66 / g-C3N4, indicating its good reusability and chemical stability. After 5 cycles, the dimethyl phthalate degradation rate of 0.6-UiO-66 / g-C3N4 / 10-SA was 57.86%; after 5 cycles, the dimethyl phthalate degradation rate of 0.6-UiO-66 / g-C3N4 / 10-SA was 93.3%. Comparative Example 4 The 0.2-UiO-66 / g-C3N4 and 0.2-UiO-66 / g-C3N4 / 10-SA were repeatedly used in cycles according to the methods of Example 2 and Example 4, respectively, and their degradation efficiency for dimethyl phthalate was recorded.

[0072] The results of this comparative example are as follows: Figure 11 As shown, after 5 cycles, the degradation rate of dimethyl phthalate in 0.2-UiO-66 / g-C3N4 was 29.78%; after 5 cycles, the degradation rate of dimethyl phthalate in 0.2-UiO-66 / g-C3N4 / 10-SA was 73.25%.

[0073] This invention constructs a UiO-66 / g-C3N4 Z-type heterojunction composite photocatalyst, utilizing the high specific surface area of ​​UiO-66 and the visible light response characteristics of g-C3N4 to enhance pollutant adsorption and promote photogenerated carrier separation. Through Z-type heterojunction design, optimized SA microsphere loading process, and innovative material ratios, a porous support is formed via Ca²⁺ crosslinking, systematically solving the industry challenges of low adsorption-catalysis synergy efficiency and difficult catalyst recovery in the treatment of low-concentration pollutants. The Z-type heterojunction suppresses carrier recombination, improving the utilization rate of photogenerated electrons and holes. The UiO-66 / g-C3N4 composite photocatalyst increases the TOC degradation rate by 2-6 times (compared to a single catalyst).

[0074] The invention uses low-cost materials (urea and sodium alginate are inexpensive raw materials) and has a simple process (calcination + hydrothermal + crosslinking), making it suitable for large-scale water treatment scenarios, such as deep treatment in sewage treatment plants and groundwater remediation.

[0075] This invention combines UiO-66 (high specific surface area MOF) with g-C3N4 (visible light responsive semiconductor) to form a built-in electric field. Figure 1f), which allows photogenerated electrons to migrate from the conduction band of UiO-66 to the valence band of g-C3N4, effectively suppressing carrier recombination while retaining strong redox capabilities (such as the ability to generate ·OH and ·O2⁻). Existing heterojunctions (such as type II) typically sacrifice carrier redox capabilities to promote separation, while the Z-type structure of this invention combines separation efficiency with strong oxidation capabilities, making it a non-obvious technical choice.

[0076] This invention uses SA as a carrier, utilizing its abundant -OH / -COOH groups to crosslink with Ca²⁺ to form a three-dimensional network structure, thereby immobilizing UiO-66 / g-C3N4 on the surface and within the pores of the microspheres. Figure 4 This method solves the problems of easy agglomeration and difficult recovery of powder catalysts. By controlling the mass ratio of SA to catalyst (preferably 10:1), the adsorption sites and photoactive sites are balanced, avoiding the decrease in activity caused by excessive coating of the support.

[0077] In a 0.1 mg / L dimethyl phthalate solution, the mineralization rate of the UiO-66 / g-C3N4 photocatalyst was >63% after 120 min, significantly higher than that of pure g-C3N4 (27.2%) and UiO-66 (9.8%). The removal rate of the 0.6-UiO-66 / g-C3N4 / SA photocatalyst was >93% within 60 min. Figure 6 a). Compared with traditional photocatalysts (such as P25), it exhibits superior mass transfer-catalytic synergy in the treatment of low-concentration pollutants. The degradation efficiency remains at 89.09% after 12 cycles. Figure 10 The concentration of the SA microspheres was significantly higher than that of the unloaded UiO-66 / g-C3N4 (<50%), demonstrating that the SA microspheres effectively prevented catalyst loss and structural damage.

[0078] This invention maintains a removal rate of >80% in water bodies containing coexisting ions such as humic acid (50 μmol / L), Cl⁻ (50 μmol / L), and Fe³⁺ (50 μmol / L). Figure 8 c). It exhibits stability in ultrapure water, tap water, well water, and secondary effluent. Figure 9 This breaks through the limitation of traditional photocatalysts being sensitive to water quality.

[0079] The above description is only a preferred embodiment of the present invention. It should be noted that for those skilled in the art, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.

Claims

1. The application of a UiO-66 / g-C3N4 / SA photocatalyst in the removal of dimethyl phthalate from wastewater, characterized in that, The preparation method of the UiO-66 / g-C3N4 / SA photocatalyst includes the following steps: g-C3N4 was added to a UiO-66 precursor solution and reacted in a reactor at 120°C for 24 hours. After washing and drying, UiO-66 / g-C3N4 was obtained. The mass ratio of UiO-66 to g-C3N4 was 0.6-1.

0. UiO-66 / g-C3N4 was dispersed in an aqueous sodium alginate solution and added dropwise to a collection solution containing calcium ions. After standing and crosslinking, the mixture was washed to obtain the UiO-66 / g-C3N4 / SA photocatalytic functional material. The concentration of the aqueous sodium alginate solution was 10-16 g / L, and the mass ratio of sodium alginate to UiO-66 / g-C3N4 was 10-16. The surface of the UiO-66 / g-C3N4 / SA photocatalyst had wrinkles and stripes.

2. The application as described in claim 1, characterized in that, The preparation steps of g-C3N4 are as follows: urea is placed in a crucible and heated at 0.5℃·min -1 The temperature was increased to 550℃ and held for 3 hours. After cooling to room temperature, the product was washed with deionized water and ethanol. After centrifugation, the resulting pale yellow product was dried under vacuum at 60℃ for 8 hours to obtain a pale yellow powder, namely pure phase g-C3N4.

3. The application as described in claim 1, characterized in that, The preparation steps of UiO-66 are as follows: terephthalic acid is dissolved in N,N-dimethylformamide, and glacial acetic acid is slowly added dropwise after stirring; zirconium chloride is dissolved in N,N-dimethylformamide and stirred; the two solutions are mixed and transferred to a reaction vessel lined with polytetrafluoroethylene, kept at 120°C for 24 hours, washed with N,N-dimethylformamide and ethanol, and then vacuum dried at 60°C for 8 hours to obtain pure phase UiO-66.

4. The application as described in claim 1, characterized in that, The mass ratio of UiO-66 to g-C3N4 is 0.

6.

5. The application as described in claim 1, characterized in that, The mass ratio of sodium alginate to UiO-66 / g-C3N4 is 10.

6. The application as described in claim 1, characterized in that, The UiO-66 / g-C3N4 / SA photocatalyst was added to a water body containing dimethyl phthalate; the dosage of the UiO-66g-C3N4 / SA photocatalyst was 1-3 g / L.

7. The application as described in claim 6, characterized in that, Photocatalytic degradation was carried out under a light source with a wavelength of 300-780nm.